Glimpsing the Impact of COVID19 Lock-Down on People With Epilepsy: A Text Mining Approach - Lanzone, Jacopo; Cenci, Cristina; Tombini, Mario; Ricci, Lorenzo; Tufo, Tommaso; Piccioli, Marta; Marrelli, Alfonso; Mecarelli, Oriano; Assenza, Giovanni (Frontiers in Neurology, 2020)
Objectives: To describe how the recent lock-down, related to SARS-COV-II outbreak in Italy, affected People With Epilepsy(PwE), we designed a survey focused on subjective reactions. Using Natural Language Processing (NLP), we analysed words PwE and People without Epilepsy (PwoE) chose to express their reactions . Methods: As a subset of a larger survey, we collected from both PwE (427) and PwoE (452) single words (one per subject) associated to the period of lock down. The survey was spread thanks to the efforts of Italian league against epilepsy Foundation during the days of maximum raise of the pandemic. Data were analysed via bag of word and sentiment analysis techniques in R. Results: PwoE and PwE showed significantly different distribution in word choice (X2, p=4.904e-13). A subset of subject used positive words to describe this period, subjects with positive feelings about the lock down were more represented in the PwE group (X2, p=0.045). Conclusion: PwoE developed reactive stress response to the restrictions enacted during lock-down. PwE, instead, chose words expressing sadness and concern with their disease. PwE appear to internalize more the trauma of lock down. Interestingly PwE also expressed positive feelings about this period of isolation more frequently than PwoE. Our study gives interesting insights on how People with Epilepsy react to traumatic events, using methods that evidence features that do not emerge with psychometric scales.